The important and effect of transfer of employees - Ismail, Fadillah; Mukhtar, Nurul Hidayah; Abdul Kadir, Adibah; Ali Hassan Humaid Alhosani, Adnan; Atan @ Yaakub, Siti Anisah (Penerbit UTHM, 2020)
The transfer of employees is a procedure of level development of individuals starting with one position to another position and without involving significant changes in their obligations, skills needed, or remuneration. It is a type of interior versatility, where the worker is moved starting with one occupation them onto the next generally at an alternate unit, area and division. This can likewise be defined as an alteration in the activity inside the organization where the new position or occupation is considerably equivalent to the old as far as pay, responsibilities, and status (Abomeh, & Mohammed, 2016). The employee transfer can be brief or permanent one, and it is started by any of the two such as employer or worker.